Determinants of Firm Value: Empirical Evidence from Companies with the Largest Market Capitalization - Pramusinta Hermawati; Maria Goreti Kentris Indarti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of profitability, company growth, capital structure, and activity ratios, particularly total asset turnover (TATO), on company value in companies listed on the Indonesia Stock Exchange with the largest market capitalization. Secondary data were obtained from the companies' annual financial reports and analyzed using multiple linear regression. The results of the study indicate that the profitability variable has a positive and significant effect on firm value, while firm growth, total asset turnover, and capital structure do not affect firm value. Additionally, capital structure acts as a moderating variable that influences the relationship between profitability, firm growth, and total asset turnover on firm value.